2017
DOI: 10.18632/oncotarget.19046
|View full text |Cite
|
Sign up to set email alerts
|

Notch system is differentially expressed and activated in pituitary adenomas of distinct histotype, tumor cell lines and normal pituitaries

Abstract: Pituitary adenomas are among the most frequent intracranial neoplasms and treatment depends on tumor subtype and clinical features. Unfortunately, non responder cases occur, then new molecular targets are needed.Notch system component expression and activation data are scarce in pituitary tumorigenesis, we therefore aimed to characterize Notch system in pituitary tumors of different histotype. In human pituitary adenomas we showed NOTCH1-4 receptors, JAGGED1 ligand and HES1 target gene expression with positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 65 publications
(90 reference statements)
2
13
0
3
Order By: Relevance
“…Xenotransplant tissue or GH3 cells cultured in vitro were processed for recovery of total RNA using TRIzol reagent (Invitrogen). Reverse transcription was performed as previously described (Perrone et al 2017).…”
Section: Rna Extraction and Cdna Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Xenotransplant tissue or GH3 cells cultured in vitro were processed for recovery of total RNA using TRIzol reagent (Invitrogen). Reverse transcription was performed as previously described (Perrone et al 2017).…”
Section: Rna Extraction and Cdna Synthesismentioning
confidence: 99%
“…We recently found that all four Notch receptors are expressed in the pituitary gland and also demonstrated enhanced gene expression of the Notch ligands Jag1 and Dll1, and the target gene Hey1, as well as activated Notch2 intracellular domain N2ICD in the somatolactotrope cell line GH3 compared to normal rat pituitaries (Perrone et al 2017). Furthermore, in prolactinomas harbored by lacDrd2KO female mice an activated Notch signaling pathway was found (Perrone et al 2017). Therefore, in the present study, we undertook a functional approach to evaluate Notch participation in pituitary adenoma growth.…”
Section: Introductionmentioning
confidence: 99%
“…The NOTCH pathway can be either activated or suppressed depending on pituitary tumor histotype ( 46 ). For instance, NOTCH3 and JAG1 expression was found upregulated in NFPA in comparison to normal human pituitary tissue ( 47 49 ).…”
Section: Aberrant Activity Of Stem Cell Regulatory Pathways In Pituitmentioning
confidence: 99%
“…Interestingly, CD133 and dopamine D2 receptor (D2R) expression, analyzed by FACS, segregate in different subpopulations (93). In another series of human PAs, NOTCH 1-4 receptor subtypes, and their ligand JAGGED1 were detected by RT-PCR, suggesting the presence of a constitutive autocrine/paracrine NOTCH system activation in a subset of tumor cells (94). In this study, NOTCH3 immunohistochemistry showed that NFPAs, prolactinomas, GHomas, and ACTH-secreting PAs (ACTHomas) express the protein in the cytoplasm and membrane of tumor cells.…”
Section: Stem Cell Markers In Histological Pituitary Adenoma Preparatmentioning
confidence: 99%